Training of Trainers (ToT) on Climate-Smart Agriculture Basics Course Module - Ekepu, David; Majaliwa, Jackson Gilbert Mwanjalolo; Nakayiwa, Florence Mayega (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
As part of the AICCRA, the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) are tasked to develop curricula and training materials to accelerate the mainstreaming of Climate Information Services (CIS) and Climate- Smart Agriculture (CSA) into University’s curricula in Africa. This report documents the training of trainers’ (ToT) workshop on Climate-Smart Agriculture Basics course module. The overall objective of the training of trainers’ workshop was to increase awareness and scale adoption/integration of the module on Climate-Smart Agriculture Basics across the RUFORUM Network and other non-AICCRA countries. 304 (Male=221; Female=82, Prefer not to say=1) participants from universities in 23 countries attended the training. The module is aimed at contributing towards promotion of the CSA approach among researchers, academia and practitioners. It introduces the concept of Climate-Smart Agriculture, the various CSA practices in Africa, the approach and tools for implementation and scaling of CSA practices, and discusses the barriers and enablers of adoption and scaling of CSA. The training increased awareness among academic staff in RUFORUM member universities. Participants indicated strong interest in incorporating the training material into their university curricula and cited several approaches including workshops, seminars, short courses and field demonstrations of the practical aspects of the module.